Respon Pemberian Pupuk Petroganik Terhadap Pertumbuhan Dan Produksi Beberapa Varietas Tanaman Mentimun (Cucumis sativus l.) Di Desa Besar II Terjun Serdang Bedagai - Anggi Andini; Eri Samah; Dini Mufriah (Universitas Teuku Umar, 2023)
In this research, we wanted to see the response of applying petroganic fertilizer to the growth and production of several varieties of cucumber (Cucumis sativus L.) in Besar II village, Terjun Serdang Bedagai. The study was conducted by a factorial Randomized Block Design (RBD), with two factors namely: Petroganic Fertilizer Factor (P) with 4 levels, namely: P0= 0 kg/plot (Control), P1= 0.5 tons/ha (50 gram/plot), P2= 1 ton/ha (100 gram/plot) (recommended dose), P3= 1.5 ton/ha (150 gram/plot), Cucumber Variety Factor (V) with 2 levels, namely V1= Harmoni Plus, V2= Monas F1. The growth of cucumber plants due to petroganic fertilizers showed a significant effect on plant height, stem diameter at plant ages 15, 30 and 45 days after planting, fruit length at 45 and 50 days after planting, fruit weight at 40, 45 and 50 days after planting. Petroganic fertilizer had no significant effect on fruit length 40 days after planting. The best petroganic fertilizer treatment is P3 which is 150 gram/plot. The growth of cucumber plants due to the variety treatment showed no significant effect on all parameters, namely plant height and stem diameter at the age of 15, 30 and 45 days after planting and fruit length and fruit weight at 40, 45 and 50 days after planting. The best variety treatment was V2, namely the Monas F1 variety. The interaction between the petroganic fertilizer treatment and the variety treatment had no significant effect on all observed parameters.